The High-Low Intraday Performance of Initial Public Offerings during Global Financial Crisis : Evidence from Malaysian Stock Market - Leow, Hon-Wei; Lau, Wee-Yeap (The Indonesian Capital Market Review, 2018)
This study investigates the high-low intraday Performance of Initial Public Offering (IPO) during Global Financial Crisis (GFC) from January 2006 to December 2011. Models comprise of hierarchical and dummy variable regressions are evaluated. Our results show: Firstly, it can be observed that intraday IPOs performance are generally lower due to the GFC; Secondly, investors receive 7 to 30 percent IPO intraday returns on average in the first trading day of pre-GFC, -5 to 11 percent during GFC, and -4 to 14 percent in the post-GFC; and thirdly, the GFC does not act as a moderator that worsens the relationship between intraday IPO performance and oversubscription ratio. As for implication, this study dispels the notion that investors should totally shun IPO during GFC period as there are still positive intraday returns among the IPOs.